Silver staining (Campbell-Switzer) of neuronal [alpha]-synuclein assemblies induced by multiple system atrophy and Parkinson's disease brain extracts in transgenic mice - Lavenir, Isabelle; Passarella, Daniela; Masuda-Suzukake, Masami; Curry, Annabelle; Holton, Janice L; Ghetti, Bernardino; Goedert, Michel (Acta neuropathologica communications, 2019)
Synucleinopathies [Parkinson's disease (PD), dementia with Lewy bodies (DLB) and multiple system atrophy (MSA)] share filamentous [alpha]-synuclein assemblies in nerve cells and glial cells. We compared the abilities of brain extracts from MSA and PD patients to induce neuronal [alpha]-synuclein assembly and neurodegeneration following intracerebral injection in heterozygous mice transgenic for human mutant A53T [alpha]-synuclein. MSA extracts were more potent than PD extracts in inducing [alpha]-synuclein assembly and in causing neurodegeneration. MSA assemblies were Campbell-Switzer- and Gallyas-silver-positive, whereas PD assemblies were only Campbell-Switzer-positive, in confirmation of previous findings. However, induced [alpha]-synuclein inclusions were invariably Campbell-Switzer-positive and Gallyas-negative, irrespective of whether MSA or PD brain extracts were injected. The [alpha]-synuclein inclusions of non-injected homozygous mice transgenic for A53T [alpha]-synuclein were also Campbell-Switzer-positive and Gallyas-negative. These findings demonstrate that transgene expression and its intracellular environment dominated over the silver staining properties of the conformers of assembled [alpha]-synuclein. Keywords: [alpha]-Synuclein, Multiple system atrophy, Parkinson's disease, Seeding, Silver staining, Transgenic